Toxic Epidermal Necrolysis - Syed Naveed Ali Shah, Ifaza Tariq, Muhammad Nauman Zafar (Journal of Rawalpindi Medical College, 2020)
Toxic epidermal necrolysis (TEN) is the most severe form of drug-induced skin reaction and includes denudation of >30% of total body surface area. The mechanism of disease is not completely understood, but immunologic mechanisms, cytotoxic reactions, and delayed hypersensitivity seem to be involved. Drug-induced toxic epidermal necrolysis (TENS), also known as Lyell’s syndrome, remains one of the most dramatic dermatological emergencies characterized by extensive destruction of epidermis and mucosal epithelia that often can be caused by drugs. TEN affects between 0.4 and 1.5 cases per million people every year with a mortality rate between 15% to 40%, with a large portion of patients dying from infections or multi-organ failure.1-4 The pathogenesis of drug-induced TEN is unknown, although several theories have been developed. Recent discoveries have shown that keratinocytes in TEN undergo apoptosis, not simply necrosis.5,6 Further research has elucidated that this apoptosis can be induced by interactions between cell surface death receptor Fas and its ligand, FasL or CD95L. The management of these patients is primarily supportive, although the use of corticosteroids and intravenous immunoglobulin (IVIG) therapy has been widely used with controversy. We report a case of risperidone induced toxic epidermal necrolysis with excellent response to corticosteroid.